(untitled) (Quinto Sol, 2010)
In this paper, transformations of internal links within the indigenous political field are explored, focusing on the last decades of the frontier. This period, in which the state progresses towards its political unification and institutional consolidation, state policies regarding Indian people show a more unified profile and aim to create the conditions necessary for the frontiers advance. The peace treaties policy, extended to almost the whole indigenous map, will be one of the devices through the state will attempt to canalize and to order its relations with different chiefs and groups. Our interest attempts to identify the probable conditionings and influences of this policy on the indigenous population at the conformation, strengthening and weakening of their political alliances. We intend specifically to reconstruct –within this context– the process of the Calfucurá´s leadership, to identify the impact of state interventions over the extent of his political summoning capacity during this period.